Accuracy Estimation of GPS Receiver Parameters with Simulator in Dynamic Mode - Kluga, A.; Zelenkov, A.; Grab, E.; Belinska, V. (Elektronika ir Elektrotechnika, 2009)
The paper reveals results of satellite system users’ devices testing in dynamic mode using signal simulator STR4500. Testing was made in the laboratory with metallized window glass and in reflectionless camera SAC3. Testing results have shown the possibility to determine parameters of user devices and dependence of accuracy of user device parameters and movement mode. For accuracy parameters estimation in dynamic mode we used 4 GPS receivers of the different kind: Graymark GPS-101, Garmin GPS-72, Garmin eTrex, Holux GR-213. The movement was simulated with two different velocities – 180 km/h and 800 km/h. It was also simulated in two orthogonal directions – to the North and to the East from Riga (total 4 scenarios). The following parameters were estimated: fix position error in horizontal plane (radial error), its mean value and Root Mean Square (RMS) deviation, as well as current velocity error, its mean value and RMS. Ill. 10, bibl. 3 (in English; abstracts in English, Russian and Lithuanian).